LEVEL OF LAW ENFORCEMENT OFFICERS’ PHYSICAL AND MENTAL HEALTH AT THE INITIAL STAGE OF THEIR PROFESSIONAL TRAINING - Holovanova, I.A.; Okhrimenko, I.М.; Lyakhova, N.A.; Penkova, N.E.; Bandurka, S.S.; Hresa, N.V.; Shylina, A.A. (World of Medicine and Biology, 2023)
The purpose of the study was to investigate the level of physical and mental health of law enforcement officers at the initial stage of their professional training. The study involved first-time certified law enforcement officers of different categories who studied at the initial professional training courses in 2021. The level of law enforcement officers’ physical health was assessed by the indicators of their morphological development and functional status. The level of law enforcement officers’ mental health was assessed by the indicators of their emotional state and professionally important psychophysiological qualities. The insufficient level of physical and mental health of first-time certified law enforcement officers of all three categories was revealed. Most of the studied indicators of law enforcement officers correspond to average or below average levels. Officers of the 3rd category revealed the worst level of indicators of morphological development, functional status, emotional state and psychophysiological qualities. The conducted research necessitates the search for effective ways to improve the training of newly certified law enforcement officers at the initial stage of professional training in order to improve their physical and mental health, especially law enforcement officers of the 3rd category.
Keywords: physical health; mental health; law enforcement officers; initial professional training